Editorial - Mani Man Singh Rajbhandari (Journal of Interdisciplinary Sciences)
Dear Readers, The journey of publishing and publication is never a final destination. Once a publication is released, we have another destination to prepare for. The motivation towards consistent publication is a drive derived from the author(s), who wishes to disseminate their valuable knowledge through the Journal of Interdisciplinary Sciences (JIS) platform. JIS has always been interested to enhance its capacity by assimilating the publication from multi-disciplinary areas. It is our belief that the readers from multi-disciplinary areas can reach the articles of their interest published under one open access platform. In this current publication, Volume 6, Issue, 1, papers are published within the areas of philosophy, psychology, music and literature. Our next issue will be published in November 2022 for which we invite researchers, managers, leaders, scientists, students and others for paper submission. The call for paper submission is also announced in the journal’s announcement portal http://journalofinterdisciplinarysciences.com/announcement/ The Journal of Interdisciplinary Sciences (JIS) is an online open access journal, which offers free submissions, free publication and open access to download its published research paper from the journal’s website http://journalofinterdisciplinarysciences.com/ It is recommended that all author(s) submitting their manuscript to JIS are advised to read the author guidelines from the journal website http://journalofinterdisciplinarysciences.com/submit-your-papers/authors-guidelines/ Let us join and collaborate together to ENRICH the BEAUTIFUL MINDS TOWARDS INTELLIGENT MINDS Mani Man Singh Rajbhandari. Ph.D. Founder and Editor-in-Chief Journal of Interdisciplinary Sciences (JIS) www.journalofinterdisciplinarysciences.com